2005
DOI: 10.1118/1.1845031
|View full text |Cite
|
Sign up to set email alerts
|

Is the diaphragm motion probability density function normally distributed?

Abstract: During radiotherapy treatment planning, the margins given to the clinical target volume to form the planning target volume accounts for internal motion and set-up error. Most margin formulas assume that the underlying distributions are independent and normal. Clinical data suggests that the set-up error probability density function (pdf) can be considered to have an approximately normal distribution. However, there is evidence that internal motion does not have a normal distribution. Thus, in general, a convol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…For the overall distribution, the normal distribution also had a good correlation with respiratory motion. George et al 41 have also shown that the overall population pdfs of the respiratory motion of the diaphragm can be approximately normal.…”
Section: Discussionmentioning
confidence: 93%
“…For the overall distribution, the normal distribution also had a good correlation with respiratory motion. George et al 41 have also shown that the overall population pdfs of the respiratory motion of the diaphragm can be approximately normal.…”
Section: Discussionmentioning
confidence: 93%
“…If a patient breathes somewhat regularly, then we would expect to see the 'bowl-shaped' pmf in figure 5 (Lujan et al 1999). However, after many treatment days, the overall pmf may start to resemble a Gaussian distribution (George et al 2005, Engelsman et al 2005 due to differences in breathing patterns from day to day ('realized pmf' in figure 5). Thus, the principle behind applying the robust methodology in practice is as follows.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reliability of this method depends on the reproducibility of the tumor motion PDF, which has not been widely studied owing to the difficulty in monitoring tumor motion with high temporal resolution and sufficient imaging time. Using a relatively short (30 s) fluorescent X-ray imaging sequence and audio/video coaching, George et al (24) showed that the combined diaphragm motion PDF approximated a normal distribution. However, the individual PDF in general did not follow a normal distribution.…”
Section: Discussionmentioning
confidence: 98%